PREVALÊNCIA DO TRANSTORNO DO DÉFICIT DE ATENÇÃO E HIPERATIVIDADE EM ESCOLAS PÚBLICAS DE SÃO LUÍS DO MARANHÃO - Reis, Tertuliana Medeiros Mota dos (2012)
The disorder and attention deficit hyperactivity disorder (ADHD) is a neurobehavioral syndrome more common at school age. It is characterized according to the criteria of the Fourth Edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) by: a persistent pattern of inattention, hyperactivity and impulsivity in at least two different contexts, thus impairing the relationship and / or learning. The recognition of symptoms by parents and teachers provides early diagnosis and therefore an appropriate multidisciplinary intervention to prevent serious academic problems and social and familiar. Objective: Evaluate the prevalence of Attention Deficit Disorder and Hyperactivity in children from public schools, city of Sao Luis - Maranhao Methods: This was an analytical cross-sectional study with a sample population of 266 students, from November 2010 to May 2011, 4 Municipal Public Schools using the criteria of the Fourth Edition of the Diagnostic Statistical Manual of Mental Disorders by the SNAP-IV questionnaire and subsequent semi-structured clinical interview.Results: We evaluated 266 children in the period November 2010 to May 2011, with a mean age of 7.79 ± 0.96 years, and 145 (54.51%) males and 121 (45.49%) female. Observed Disorder and Attention Deficit Hyperactivity Disorder in 19 students (7.14%), predominantly male (78.95%) and 9 (47.37%) the inattentive type, 7 (36.84 %) of the type and hyperactive 3 (15.79%) mixture. As for oppositional defiant disorder, was identified in eight of 19 children diagnosed with Attention Deficit Disorder / Hyperactivity (42.11%). Conclusion: The prevalence of Attention Deficit Disorder and Hyperactivity was 7.14%, with male predominance and the inattentive type. The oppositional defiant disorder, was identified in 42.11% of children with Attention Deficit Disorder and Hyperactivity.